Exploring extensions of the Subramanian–Deaton cost per calorie approach: Imputing nutrient intake from foods prepared and consumed away from home and other composite foods - Mwangi, Dena M.; Fiedler, John L.; Sununtnasuk, Celeste (International Food Policy Research Institute, 2017)
This paper assesses the Subramanian and Deaton (S–D) approach for imputing the caloric intake of households from food prepared away from home (FAFH) and composite foods (CF) by juxtaposing it with the imputations of alternative approaches, and extends these approaches to four additional nutrients—vitamin A, iron, zinc, and calcium. The apparent relative nutritional insignificance of FAFH and CF in Bangladesh obfuscates our efforts to assess alternatives to the S–D approach to imputation, and we remain uncertain about the relative value of the alternative imputation approaches examined. FAFH and CF—although widely consumed in Bangladesh—constitute a relatively unimportant source of nutrients, regardless of how the nutrient content of FAFH and CF is imputed.